2017
DOI: 10.1016/j.celrep.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Death following Influenza Vaccination Initiates the Inflammatory Response that Promotes Dendritic Cell Function in the Draining Lymph Node

Abstract: The mechanism by which inflammation influences the adaptive response to vaccines is not fully understood. Here, we examine the role of lymph node macrophages (LNMs) in the induction of the cytokine storm triggered by inactivated influenza virus vaccine. Following vaccination, LNMs undergo inflammasome-independent necrosis-like death that is reliant on MyD88 and Toll-like receptor 7 (TLR7) expression and releases pre-stored interleukin-1α (IL-1α). Furthermore, activated medullary macrophages produce interferon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 50 publications
3
55
2
1
Order By: Relevance
“…IL-1 α release from lymph node macrophages in an inflammasome-independent death event has been shown to enhance antigen presentation and humoral responses to influenza vaccination. 45 IL-1 α has been shown to initiate lung inflammation in a model of sterile inflammation using silica. 46 Recently, some reports have suggested IL-1 α rather than IL-1 β drives sepsis pathology.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 α release from lymph node macrophages in an inflammasome-independent death event has been shown to enhance antigen presentation and humoral responses to influenza vaccination. 45 IL-1 α has been shown to initiate lung inflammation in a model of sterile inflammation using silica. 46 Recently, some reports have suggested IL-1 α rather than IL-1 β drives sepsis pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that vaccinia virus induces inflammasome activation and death of SCS macrophages by pyroptosis. This results in release of extracellular ASC specks which drive lymph node inflammation ( 39 ), while other work using an attenuated influenza vaccine has shown a role for TLR7 signaling in the death of SCS macrophages and subsequent IL-1α release ( 40 ). The previously shown partial reduction of ISCOMATRIX adjuvant activity in ASC and caspase- 1/11 deficient mice, and the ISCOMATRIX driven in vitro death of macrophages in combination with our data suggests that SCS macrophages may be a key point where innate immune activation plays a role in mediating ISCOMATRIX adjuvant activity ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-Photon Intravital Video Microscopy (MP-IVM), in combination with image-based systems biology 1 , represent a key methodology for studying the interplay of cells in organs and tissues of living animals 2 . Indeed, recent analyses of leukocyte migration in MP-IVM data, highlighted unprecedented cell-to-cell interaction patterns such as antigen capturing 3 and presentation 4 , host-pathogen interaction 5 , 6 , tumor immune surveillance 7 and cell activation 8 amongst others. The advantage of MP-IVM with respect to other optical methods relies on the usage of multiple infrared photons.…”
Section: Background and Summarymentioning
confidence: 99%